Pemanfaatan Limbah Karet Tambal Ban (Kompon) Sebagai Bahan Tambah Pada Campuran Aspal Panas Menggunakan Metode Durasi Perendaman - Sibala, Teofilus Riyandi; Nurdin, Abdul. Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
A thin layer of asphalt concrete (lataston) is a cover layer which consist of a mixture of gap graded aggregate, filler and hard asphalt with certain ratio; which is mixed and compacted heat (within a certain minimum temperature of 124ºC), The purpose of the study is to determine the effect of addition of rubber patch on the Marshall characteristics of the hot asphalt mixture using the immersion duration method. The study uses waste rubber tires with the addition of 4%, 6%, and 8%. Samples of specimens were made as many as 48 samples, 15 normal samples, 6 remaining KAO samples and 27 variations samples. Treatment of the specimens was carried out with a duration of immersion of 7, 14 and 21 days. The manufacture of test objects is hot mixed and refers to the 2018 Bina Marga Specifications; the test was carried out with the Marshall tested equipment. The results of the test indicate that the effect of tire rubber waste as an additive in hot asphalt mixtures  with the immersion duration method can result in a decrease in the value of the asphalt mixture properties.